Automatic head detector nootebook fan / Muhammad Safwan Ab Rashid & Muhammad Syakir Ahmad Bakhari - Ab Rashid, Muhammad Safwan; Ahmad Bakhari, Muhammad Syakir (2015)
This project is designed to upgrade the older notebook fan in the market which it fan cannot be regulate when sense heat above normal temperature. Theoretically, when the thermistor detect any heat surrounding, the fan will automatically operate. This typeof project is using integrated circuit (IC) type 741 which is a wide range of analog application. This device is designed to operate from a wide range of power supply voltages. Besides that, this circuit use an NTC (Negative temperature coefficient)which is a thermistor is one in which the zero-power resistance decreases with an increase in temperature. This device will locate directly below the notebook to sense heat. Thus, make the DC fan to turn ON and when the temperature become cold or below the normal temperature, the DC fan will tum OFF by it self. Moreover, as usual, a relay is included in the circuit to connect with the output. It will active when there is current flow through it.